Ecclesial Visibility as a Byproduct of Discipleship: Dietrich Bonhoeffer's Understanding of the Visible Church and Its Ecumenical Implications - Jodon, Cole Christian (Pro ecclesia, 2020)
This article provides an account of Bonhoeffer's understanding of church visibility, and considers the implications that account has for the contemporary Catholic-Lutheran dialogue. By tracing the roles of divine and human agency within Bonhoeffer's understanding of church visibility, the article argues that Bonhoeffer understands church visibility as a byproduct of discipleship. Applied to the Catholic-Lutheran dialogue, such an account implies that church visibility ought not be a goal of the dialogue, but rather an inevitable byproduct of discipleship to Christ which takes place as Christians follow after Christ together.